Polydopamine coated clay for coating on polymers - Sum, Samantha Ying Ying. (2013)
Widespread applications of polymers in our daily lives have brought about interests in the field of polymer coatings, most of which serve a single purpose. Polymer coatings are used either as a mechanical protection layer on softer polymers, or a protection against corrosion and photo-oxidation on metals or other functional materials. Most of the existing forms of polymer coatings can only serve a single purpose at a time, and with the increasing range of applications of polymers, it is necessary to have a multifunctional polymer coating.